2021
DOI: 10.33546/bnj.1524
|View full text |Cite
|
Sign up to set email alerts
|

Using a mobile application (“PrimaKu”) to promote childhood immunization in Indonesia: A cross-sectional study

Abstract: Background: Universal immunization coverage among children in Indonesia is low compared to the global target. Many children in Indonesia are not fully immunized as recommended by the government, which results in a high mortality rate. The government has developed a mobile application (PrimaKu) to provide information on vaccinations and reminder features. However, the successful use of the immunization features of the app has not been widely studied.Objective: This study aimed to evaluate the use of PrimaKu on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A significant concern in child mortality and morbidity is the poor level of vaccination, either because of fear of the side effects caused by the vaccine, lack of health centers in the area where the family lives, forgetfulness, lack of knowledge, poor information received, insufficient health education or indifferent on the part on the infant's parents/caregivers of the infant, which is why mobile applications are being developed whose function is to remind parents of child vaccination [14,22,25,26,27,28,29,31,32,34,36,37,38,39,41,42,43,45,46,47,49,50,51,52]. However, it is also being used as a vaccine safety control [53] and even more so with the issue of new vaccination technologies applied to COVID-19.…”
Section: P1 What Aspects Promoted the Development Of Mobile Applicati...mentioning
confidence: 99%
See 4 more Smart Citations
“…A significant concern in child mortality and morbidity is the poor level of vaccination, either because of fear of the side effects caused by the vaccine, lack of health centers in the area where the family lives, forgetfulness, lack of knowledge, poor information received, insufficient health education or indifferent on the part on the infant's parents/caregivers of the infant, which is why mobile applications are being developed whose function is to remind parents of child vaccination [14,22,25,26,27,28,29,31,32,34,36,37,38,39,41,42,43,45,46,47,49,50,51,52]. However, it is also being used as a vaccine safety control [53] and even more so with the issue of new vaccination technologies applied to COVID-19.…”
Section: P1 What Aspects Promoted the Development Of Mobile Applicati...mentioning
confidence: 99%
“…Studies found Registration and monitoring [22], [33], [42] Access to information [22], [25], [40], [42], [44], [47], [26] Increasing coverage [22], [24], [14], [26], [29], [30], [35], [39], [42], [47], [52], [29], [46], [48], [50] Reminders [22], [14], [25], [26], [27], [28], [29], [31], [32], [34], [36], [37], [38], [39], [41], [42], [43], [45], [46], [47], [49], [50], [51], [52] Education [25],…”
Section: Aspectsmentioning
confidence: 99%
See 3 more Smart Citations